Comunicadoras y periodistas ecuatorianas: alternativas para enfrentar el ciberacoso en el entorno digital (Tema Central) - Carrera Pacheco, María José (2019)
Technology in journalism has modified its practices of production, dissemination and information consumption. It has also considerably transformed the relationship between journalists, media, sources and readers. The most common interaction tools between journalists and digital users are social networks, spaces that, in addition to encouraging participation and contribution to generate content, have led to the appearance of violent demonstrations against information professionals, mainly women. The present study details the data obtained from a survey applied to several information professionals, who consider their job as risky, in addition to stating that there is harassment, which is expressed both physically and digitally. Specialists were interviewed, who propose strategies to face the problem of harassment and violence in social networks. Methodologically, a netnography was applied, which included observing the Twitter account of three journalists, in order to identify the terms most frequently used to attack them.